Transmission of West Nile Virus from an Organ Donor to Four Transplant Recipients - Martha Iwamoto; Daniel B. Jernigan; Antonio Guasch; Mary Jo Trepka; Carina Blackmore; Walter C. Hellinger; Si M. Pham; Sherif R. Zaki; Robert S. Lanciotti; Susan Lance‐Parker; Carlos A. DiazGranados; Andrea Winquist; et al. (2003)
In August 2002, fever and mental-status changes developed in recipients of organs from a common donor. Transmission of West Nile virus through organ transplantation was suspected.